PENERAPAN PENDEKATAN TEMATIK DALAM MENINGKATKAN KETERAMPILAN BERBICARA PADA SISWA KELAS IV SD NEGERI 192 MALUKU TENGAH: Indonesia - Latue, Crisma H.; Notanubun, Zainudin; Sahetapy, Sarah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve speaking skills through the application of thematic approach in fourth grade students of SD Negeri 192 Maluku Tengah. This study uses the type of class action research (PTK) using 2 cycles in which there are planning, implementation, observation and reflection. The results showed that based on the results of the first cycle test value obtained 68.20 or sufficient category, while the second cycle test results of 84.53 or very good value category. This can prove an increase from cycle I to Cycle II. The increase shows that the learning of speaking skills in students is very good.